Ambient suppression in vibration bump test using wavelet-based filter - Che Ku Eddy Nizwan, Che Ku Husin; Mohd Fairusham, Ghazali; Ahmad Razlan, Yusoff (IOP Publishing, 2020)
Abstract. Modal analysis is generally used to determine the structural dynamic characteristics of a system through experimental. The main purpose of a modal analysis is to identify the modal parameter, which consists of natural or resonant frequencies, mode shapes and damping. However, this technique required all the system in shut down condition in order to perform modal testing. The presence of ambient force such as motor unbalanced can cause errors in measurement of time response. Therefore, a study on how to improve the quality of the acquired signals in EMA is crucial in order to increase the efficiency of EMA technique under the presence of ambient force. This paper introduces a method to eliminate the ambient component in measured vibration response using the wavelet-based filter. The two experiments have been carried involving two different conditions, shutdown condition and operating condition. The sources of the ambient in operating condition are induced from a motor and speed controller cooling fan. The proposed method utilizes the discrete wavelet transform (DWT) and improvised spectral subtraction in filtering the ambient. The discrete wavelet transform (DWT) is applied to both ambient data and total response data to decompose the signal by a factor of two into several levels of the wavelet decomposition. The modification of the discrete wavelet transform (DWT) method has been done where the wavelet thresholding is replaced with the spectral subtraction to suppress the ambient in the signal. The spectral subtraction is used to suppress the ambient in each wavelet coefficient at each level of decomposition to avoid the losses of useful signal data while filtering the ambient. The decomposed wavelet signal is reconstructed and the result is being compared with the baseline data. The Frequency Response Function obtained from the reconstructed signal shows the harmonics feature from ambient excitation were successfully suppressed. The results show that the proposed approach is effective to suppress the ambient effect in vibration response measurement.